Genes, guts, and microbes: decoding host-driven microbial regulation using intestine-specific conditional knockouts - Dey, Priyankar (Frontiers in Immunology, 2025)
This narrative review underscores the influence of host genetics in actively regulating gut microbiota composition and function, highlighting the distinctive advantages of intestine-specific conditional knockout (cKO) models in gut microbiome research. In contrast to whole-body knockouts or germ-free animals, these precision models, enabled by Cre-loxP technology, eliminate confounding systemic effects to elucidate how localized host genes within intestinal cells regulate the gut microbial ecology. The review identifies three fundamental host-driven regulatory mechanisms through the analysis of specific gene deletions: (1) barrier integrity (e.g., mucus and junction proteins), (2) immune defenses (e.g., antimicrobial peptides and glycan synthesis), and (3) metabolic signaling (e.g., bile acid receptors and glucose transporter). These pathways jointly impose microbial symbiosis, and their disruption leads to dysbiosis characterized by increased abundance of pathobionts (e.g., Escherichia, Proteobacteria), directly connecting host genetics to inflammatory and metabolic disorders. This host-centric viewpoint emphasizes the gut as an active regulator, rather than a passive microenvironment for the microbiota, providing significant insights for creating tailored therapeutics that focus on host pathways to restore microbial balance in disorders such as inflammatory bowel diseases.